Challenges and prospects for implementing halal principles in the jamu industry in Indonesia - Nurrosyidah, Iif Hanifa; Syakur, Abd (Journal of Halal Product and Research (JHPR), 2024)
The traditional herbal medicine (jamu) industry in Indonesia faces challenges in applying halal principles due to the common use of non-halal ingredients in jamu production. Jamu is in high demand in Indonesia, a largely Muslim country with a thriving halal economy. This article reviews the challenges and prospects of implementing halal principles in Indonesia's jamu industry. The research methods employed include literature review and analysis of relevant regulations and industry practices in jamu production. The research findings indicate that the presence of non-halal ingredients in some jamu products poses obstacles to meeting halal requirements. The discussion proposes strategies and potential avenues to enhance the implementation of halal principles in the jamu industry, such as developing alternative raw materials and obtaining halal certification. The conclusion drawn from this article is that implementing halal principles in the jamu industry holds promising prospects but requires close collaboration between the government, producers, and other stakeholders.